Optimalisasi peran dan strategi hubungan masyarakat dalam membangun citra positif dan kepercayaan nasabah pada perbankan syariah - Fitroh, Ike Silvia (Maliki Interdisciplinary Journal, 2025)
Islamic banking continues to show rapid growth in the global financial industry, despite facing challenges in building a positive image and public trust. The public relations (PR) function plays a strategic role as a communication link between banking institutions and the public, as well as a means of education regarding Sharia principles. This study aims to examine the strategy and optimization of the role of public relations in building a positive image and increasing customer trust in Islamic banking. A qualitative approach was used through literature review and case studies to illustrate effective public relations communication practices, such as the use of digital media, social responsibility programs, and fast and responsive service. The results show that the integration of educational and innovative communication strategies is a crucial factor in strengthening customer trust and loyalty. Overall, the implementation of adaptive public relations contributes to the sustainable growth and enhanced reputation of Islamic banking..